Edukasi Tanaman Obat dan Pemanfaatannya pada Siswa SMA dan SMK Bhakti Idhata - Emilda Emilda; Nur Rizkiyah; Subhan Harie (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
This activity was carried out because the lack of knowledge about medicinal plants in SMA and SMK Bhakti Idhata students. Their knowledge about it is limited only what is taught in school. Meanwhile the knowledge about medicinal plants is very important for them, both for direct use- as the cases of degenerative diseases increase among young generation- and for conservation. Beside this is also part of the culture of Betawi people, that needs to be preserved. The purpose of it is to give the knowledge about the types and utilities of medicinal plants to students and motivate them to participate in preserving the plants around them. The method is by lectured and discussions using power point media, boolets and interspersed with games. The results of counseling was not too much of students enthusiasm with this activity, so needed to be carried out in the next with more interesting methods and media.